THE INFLUENCE OF TEACHING ENGLISH VOCABULARY USING VCD LEARNING TO THE KINDERGARTEN LEVEL IN SMART AND FUN COMMUNICATIVE ENGLISH COURSE SAMARINDA - MUJA, Ikhwanul Ahsan Faryabi (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2016)
The researcher used VCD Learning to help kindergarten level students Smart and Fun Communicative English Program Samarinda on learning English vocabulary. The contents were relevant to the vocabulary for students in kindergarten level of Smart and Fun Samarinda.This study was aimed finding whether there was significance difference between experimental and control groups and whether there was significant difference between post experimental and control groups. It is a kind of experimental research. This studyâs design was two group-pretest-treatment-posttest design. The population of this study was 60 students. The researcher took 40 students from two classes as the sample of this study. Then, took other 20 students as try out test respondents. The test was tried out to 20 respondents consisted of 30 items. After being analyzed, its reliability coefficient was 0.462. The experimental groupâs mean score on the post-test was 80.17 while on control group was 70.67. After analyzing the two mean scores by using the program of SPSS 16.0, it was found that the difference significance value between the two mean scores t - computed 4.068 was higher than t - table 2.093 with the level of significant 5%. The computation showed that the two groupsâ mean scores of significantly differed. Thus, the alternative hypothesis (Ha) is accepted and the Null Hypothesis (Ho) is rejected. It could be concluded that there was significant difference of English vocabulary achievement among students of kindergarten level of Smart and Fun by using VCD Learning.